2021
DOI: 10.1155/2021/6623794
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Variability and Concomitant Lesions in Pterygium in a Large Case Series

Abstract: Pterygium is a common lesion consisting of fleshy conjunctival growth extending towards the cornea. There is no documented risk of malignant transformation; however, concomitant disease is not rare, and its link to sunlight exposure indicates a risk of other malignancies. The purpose of our study is to describe histopathological features of resected pterygiums and to recognize patients at risk of other conjunctival diseases. One hundred and forty-nine formalin-fixed and paraffin-embedded pterygium samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Perra and colleagues reported a similar rate of 8.75% (seven out of 80 pterygia samples, five without atypia and two with atypia) from a population in Equador [15]. Perhaps more relevant to our study, melanocytic hyperplasia was found in 32% (47 of 149 pterygia lesions) with a significant correlation to chronic inflammation [16]. None of these studies performed immunohistochemistry in each case and were reliant on recognizing the lesions first with H&E staining.…”
Section: Discussionsupporting
confidence: 59%
“…Perra and colleagues reported a similar rate of 8.75% (seven out of 80 pterygia samples, five without atypia and two with atypia) from a population in Equador [15]. Perhaps more relevant to our study, melanocytic hyperplasia was found in 32% (47 of 149 pterygia lesions) with a significant correlation to chronic inflammation [16]. None of these studies performed immunohistochemistry in each case and were reliant on recognizing the lesions first with H&E staining.…”
Section: Discussionsupporting
confidence: 59%
“…Comparative characteristics are listed in Supplementary Table S1 . The 3 studies took place in different parts of the world, both inside (Sydney and Cairo) [ 26 , 27 ] and north of the pterygium belt (Montreal) [ 28 ]. In the current study, specimens were collected from individuals residing near Córdoba, Argentina, south of the pterygium belt.…”
Section: Resultsmentioning
confidence: 99%
“…A challenge for interpretation of gene expression profiling data comparing pterygium and pinguecula specimens is that these lesions have much in common pathologically, but presentation of these common features can be highly variable [ 26 , 27 , 28 ]. For this reason, it is difficult to know what is a true difference between the two pathologies, and what is only a subtype difference.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular hyperproliferation is a significant feature in pterygium [ 24 ]. and its recurrence is associated with excessive wound healing after surgery.…”
Section: Discussionmentioning
confidence: 99%